Recurrence Metrics for Assessing Eye Movements in Perceptual Experiments - Susan Farnand; Preethi Vaidyanathan; Jeff B. Pelz (Bern Open Publishing, 2016)
In a recent study evaluating the impact of image content on the consistency of eye movements in perceptual experiments (Farnand, 2013) image complexity was inversely related to scanpath consistency. This work involved a qualitative analysis of eye movements along with analysis of the number and duration of fixations. No quantitative analysis of scan path consistency was performed. Recently, Anderson et al. developed a quantitative tool - Recurrence Quantification Analysis - for analyzing eye movement patterns (Anderson et al., 2013). In the present study, the RQA method was applied to the fixation data of Farnand (2013). The results suggest that RQA analysis provides relevant quantitative information regarding the attentional focus of observers viewing pictorial images and, as such, a potentially powerfully tool for eye-tracking studies.